Pelatihan Pembuatan Antibacterial Hand Soap Ekstrak Daun Melinjo Kepada Santri Insan Cita Serang Banten - Ismi Farah Syarifah; Hurin Lathifatul Majidah; Bima Oktavianto (Universitas Muhammadiyah Semarang, 2024)
Melinjo leaves as an antibacterial hand soap have never been used. This service activity aimed to provide training in making antibacterial hand soap made from melinjo leaf extract. The method used consisted of three stages, namely partnering with Islamic boarding schools, providing education about the importance of environmental hygiene, and training in making antibacterial hand soap which was attended by students of the Insan Cita Serang (ICT) Islamic boarding school. The service activity ran successfully, which was reflected in the percentage of total participant assessments where the implementation of this activity was rated as 56%